2022
DOI: 10.37745/ijcecem.14/vol10n25266
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Covid-19 on Modal Choice Behaviour of Commuters in Metropolitan Lagos, Nigeria

Abstract: Several empirical studies on the COVID-19 pandemic have shown a large reduction in human mobility and a dramatic shift in travel patterns across all modes of transportation. Modal choice behaviour especially in developing cities with less developed transportation infrastructure have been impacted in an unprecedented manner. This paper aims to assess the impacts of covid-19 on modal choice behaviour of commuters in metropolitan Lagos. The comparison was made with the modal choice behaviour of commuters in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Human mobility patterns have changed significantly as a result of the COVID-19 pandemic ( 80 , 81 ). An online survey of commuter travel in Philadelphia showed that almost 50% of respondents changed their mode of transportation during the COVID-19 pandemic ( 82 ).…”
Section: Review Methodologymentioning
confidence: 99%
“…Human mobility patterns have changed significantly as a result of the COVID-19 pandemic ( 80 , 81 ). An online survey of commuter travel in Philadelphia showed that almost 50% of respondents changed their mode of transportation during the COVID-19 pandemic ( 82 ).…”
Section: Review Methodologymentioning
confidence: 99%